Implementation, utilization, and evaluation of a pharmacist-driven romiplostim dosing service for patients with immune thrombocytopenia at a multisite cancer centre. (April 2022) - Moore, Donald C.; Elmes, Joseph B.; Gebru, Tsion; Lavery, Lesli A.; Pellegrino, Annie; Plesca, Dragos
Introduction: Romiplostim is a thrombopoietin receptor agonist approved for the treatment of patients with chronic immune thrombocytopenia who have had an insufficient response to corticosteroids, immune globulin, or splenectomy. Dose adjustments of romiplostim are based on platelet counts and follow a dosing schema that requires frequent monitoring. As a quality improvement initiative to increase clinical efficiency and promote clinical pharmacy services at our institution, we developed a collaborative practice agreement and implemented a novel pharmacist-driven romiplostim dosing protocol. Methods: A retrospective chart review was conducted to evaluate the acceptance, utilization, and impact of the pharmacist-driven romiplostim dosing service. The primary outcome of our analysis was the adoption rate by providers of the romiplostim pharmacist dosing service. Secondary endpoints were focused on patients newly initiating romiplostim on the dosing service and included platelet responses and number of dose adjustments by a pharmacist Results: A total of 54 patients received romiplostim in our analysis: 25 patients who had already been receiving romiplostim and 29 patients who newly initiated romiplostim during the study period. Of the 29 patients newly initiating romiplostim, 27 (93%) had their dosing managed by a pharmacist Twenty-one patients (84%) and 18 patients (75%) achieved an initial and durable response with romiplostim, respectively. Pharmacists made a median of 3 dose adjustments to romiplostim per patient. Conclusion: The implementation of a pharmacist-driven romiplostim dosing service led to a significant adoption and utilization by physicians at our health system.